Graphs

Draw the graph of each of the following equations:
y = 3x – 2
y = 5x + 5
y = x – 2
x = 3y – 2
x + 6y = 12

Draw the graph of each of the following equations:
y = 3x – 2
y = 5x + 5
y = x – 2
x = 3y – 2
x + 6y = 12

Document Preview:

Draw the graph of each of the following equations:
y = 3x – 2
y = 5x + 5
y = x – 2
x = 3y – 2
x + 6y = 12

Draw the graph of each of the following equations:
y = 3x – 2
y = 5x + 5
y = x – 2
x = 3y – 2
x + 6y = 12

Attachments:


Leave a Reply

Your email address will not be published. Required fields are marked *

You may use these HTML tags and attributes: <a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>

Order Now

Top